Influence of Society for Academic Emergency Medicine Foundation's Research Training Grant on postaward academic federal funding. (10th March 2022) - Chang, Andrew K.; Lee, Sangil; Le, Rachel; Ata, Ashar; Harland, Kari; Khan, Ayesha; McMillan, Melissa; Mohr, Nick
Abstract: Objectives: The objective was to measure the impact of the Society for Academic Emergency Medicine Foundation's (SAEMF) Research Training Grant (RTG) by comparing academic success in grant recipients versus non‐recipient applicants. Our primary outcome was subsequent federal funding as a principal investigator (PI) or multiple principal investigator (MPI). Our secondary outcomes included subsequent K‐award funding, R‐series funding, R01 funding, and academic productivity measured by first author peer‐reviewed publications. Methods: The authors examined all SAEMF RTG applicants from 2002 through 2019 ( n  = 109). Data were collected using the National Institutes of Health RePORTER database, a literature search using PubMed, and an online survey sent to all RTG applicants. Relative risks (RRs) with 95% confidence intervals (95% CI) were calculated. Results: Over 18 years, 18 of 109 (16.5%) RTG applicants were awarded by SAEMF. Subsequent federal funding as PI or MPI was obtained by 11 of the 18 RTG recipients compared to 29 of the 91 nonrecipients (61% vs. 33%, RR = 1.9; 95% CI = 1.2–3.1). The RTG award was also associated with increased probability of receiving a federal Career Development Award (K‐series) (RR 2.0; 95% CI 1.1–3.9) and R‐series award (RR 2.0; 95% CI 1.1–3.9) but not an R01 award (RR 2.1; 95% CI 0.8–5.3). The median number of first‐authored peer reviewed manuscripts did not differ between RTG award recipients (14, IQR 8, 44) and nonrecipients (14, IQR 6, 30) ( p  = 0.5) though RTG recipients had a higher percentage of their publications as a first author (49% vs. 33%, p  = 0.04). Conclusions: SAEMF RTG awards were associated with increased probability of future federal funding, including career development awards and R‐series awards but not R01 awards. RTG recipients also had a higher percentage of their peer reviewed publications as first author.